Low-Cost and Eco-Friendly Calcium Oxide Prepared via Thermal Decompositions of Calcium Carbonate and Calcium Acetate Precursors Derived from Waste Oyster Shells - Somkiat Seesanong; Chaowared Seangarun; Banjong Boonchom; Nongnuch Laohavisuti; Wimonmat Boonmee; Somphob Thompho; Pesak Rungrojchaipon (Materials, 2024)
, attributed to moisture adsorption. Fourier-transform infrared (FTIR) spectroscopy identified the vibrational characteristics of the Ca-O bond. Scanning electron microscopy (SEM) showed similar morphologies for both CaO-CC and CaO-CA, with CaO-CA displaying a significant amount of rod-like crystals. Based on these results, calcium acetate monohydrate (CA) is recommended as the superior precursor for synthesizing high-purity CaO, offering advantages for various applications.
Keywords: Calcium Carbonate Crystallization and Inhibition; Materials Engineering and Processing; Chemistry and Chemical Engineering